Jalan Terjal Gerakan Lingkungan Hidup Dalam Wujud Antagonisme Paradigmatik - Fasyah, Adistya Karamina; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
Differences in forms and demands among various environmental movements in South Kalimantan, which are influenced by ideological streams, are the main obstacles in the formation of strong solidarity to achieve environmental protection goals. The research was conducted to produce a map of environmental movement streams and description of the dynamics of the environmental movement in South Kalimantan. The research used qualitative methods. Data collection techniques used observation, in-depth interviews and documentation. The results stated that there are 4 (four) streams that exist in the environmental movement in South Kalimantan, namely: institutional, functional, marxism and critical. Functional stream is the most dominating stream. Functional stream is reflected in several movements, namely Sahabat Bekantan, Borneo Urban Lab, Eco Enzyme Nusantara, Eco Fashion, Putik Bersih and WALHI South Kalimantan. There is an influence of the critical stream which is reflected in the Eco Fashion movement and the Putik Bersih movement. The influence of institutional stream is seen in the Save Meratus movement, XR Meratus, and WALHI South Kalimantan. Then, the WKR (Wilayah Kelola Rakyat) movement by WALHI South Kalimantan reflects the influence of marxism. The presence of new variants of the environmental movement in South Kalimantan has influenced the widespread understanding of environmental movement streams. Research shows that openness to various streams can strengthen the environmental movement. By combining different approaches, movements such as Putik Bersih, Save Meratus, and WALHI South Kalimantan have proven their ability to be more dynamic and responsive in facing complex environmental challenges. However, paradigm differences still hamper the birth of a collective struggle of the environmental movement in South Kalimantan.